Executive governance of EU research policy: An organisation theory perspective - Åse Gornitzka (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
The paper proceeds as follows: The first section sketches some main theoretical arguments concerning the dynamics of executive governance: first a set of arguments based on organisation theory is developed, after which we look into how policies can determine politics. The subsequent section outlines how executive governance has developed in EU research policy, reviewing the studies that form the basis for claims of technocratic dominance, segmentation and path dependence particular to EU research policy. Finally an overview is given of some main developments in the executive governance of research policy in the last decade, looking first into change and stability in its structure and capacity at the European level and then on empirical patterns of executive governance in committees and networks as evidenced in data on the Commission's expert group system.
Keywords: 320